A retrospective description of primary immunodeficiency diseases at Red Cross War Memorial Children's Hospital, Cape Town, South Africa, 1975 – 2017 - Moodley, Sashmi (Department of Paediatrics and Child Health, 2020)
Background. The primary immunodeficiency diseases (PIDs) constitute a diverse and everexpanding group of inborn errors affecting a wide range of immune functions. They are not well documented in Sub-Saharan Africa. An important barrier to care is limited awareness of PIDs and their management among health care professionals. This fascinating spectrum of diseases is rapidly expanding worldwide, and not as rare as we think. Genetic characterization and newborn screening for primary Immunodeficiency diseases (PIDs) may be the gold standard in the first world setting but are neither practical nor feasible for our doctors. Yet, other low and middle income countries in the world have also established reasonable services and created registries for children with PIDs, including other African countries. Objective. To describe the spectrum of PIDs at a tertiary paediatric hospital. Methods. A retrospective descriptive study of PIDs diagnosed at Red Cross War Memorial Children's Hospital, Cape Town, South Africa between 1975 and 2017 was undertaken. Results. 252 children with PIDs were identified, spanning 8 of the 9 categories listed in the 2017 classification of the International Union of Immunological Societies. Predominantly antibody deficiencies, combined immunodeficiencies with associated syndromic features, and immunodeficiencies affecting cellular and humoral immunity accounted for 79% of all PIDs. The mean age (standard deviation) at diagnosis was 46 (50) months and the male to female ratio was 1.5:1. A history of parental consanguinity was present in 3 children (1.2%). Recurrent infection was the most prevalent presenting phenotype, manifesting in 70.2% of the patients. Genetic or chromosomal confirmation was obtained in 42/252 (16.7%) of the children. Common interventions used to prevent infection were antimicrobial prophylaxis and immunoglobulin replacement therapy, administered to 37.7% and 36.9% of the patients respectively. Six of seven children who underwent haematopoietic stem cell transplantation (HSCT) had successful outcomes. The 7th patient died 2 months post-HSCT from overwhelming infection. Although we could not account for the children lost to follow up during the study period, 53 (21.0%) deaths were confirmed. Conclusions. Several challenges exist in the recognition and treatment of children with PIDs in our setting. These include limited access to genetic diagnostics and HSCT. Sub-optimal treatment options contribute to the overall mortality of PIDs in South Africa. Greater awareness among clinicians treating children and more laboratory diagnostic capacity are needed to increase the recognition PIDs among children in South Africa. The treatment options that are available in South Africa are unevenly distributed. Hence, treatment capacity should be expanded throughout the country, especially advanced interventions such as HSCT. Ongoing reporting of registries such as ours and increased community awareness should strengthen the lobby for greater investment in rare diseases such as the PIDs.